BRIEF 1 – Assessing the impact of Heifer Nepal programming on the use of climate-smart agriculture practices in smallholder goat farming systems - Caulfield, Mark E.; Giles, James; Sheikh, Asjad Tariq; Poudel, Avash (2023)
This brief provides insight into the different farming systems of the three study regions and their application of CSA practices, comparing uptake between Heifer supported cooperatives and non-Heifer supported cooperatives, using evidence from a Rural Household Multi-Indicator Survey (RHoMIS).